Pex11-related Proteins in Peroxisome Dynamics: A Role for the Novel Peroxin Pex27p in Controlling Peroxisome Size and Number in Saccharomyces cerevisiae - Tam, Yuen Yi C. (The American Society for Cell Biology, 2003)
Transcriptome profiling identified the gene PEX25 encoding Pex25p, a peroxisomal membrane peroxin required for the regulation of peroxisome size and maintenance in Saccharomyces cerevisiae. Pex25p is related to a protein of unknown function encoded by the open reading frame, YOR193w, of the S. cerevisiae genome. Yor193p is a peripheral peroxisomal membrane protein that exhibits high sequence similarity not only to Pex25p but also to the peroxisomal membrane peroxin Pex11p. Unlike Pex25p and Pex11p, Yor193p is constitutively expressed in wild-type cells grown in oleic acid-containing medium, the metabolism of which requires intact peroxisomes. Cells deleted for the YOR193w gene show a few enlarged peroxisomes. Peroxisomes are greatly enlarged in cells harboring double deletions of the YOR193w and PEX25 genes, the YOR193w and PEX11 genes, and the PEX25 and PEX11 genes. Yeast two-hybrid analyses showed that Yor193p interacts with Pex25p and itself, Pex25p interacts with Yor193p and itself, and Pex11p interacts only with itself. Overexpression of YOR193w, PEX25, or PEX11 led to peroxisome proliferation and the formation of small peroxisomes. Our data suggest a role for Yor193p, renamed Pex27p, in controlling peroxisome size and number in S. cerevisiae.